2021
DOI: 10.1128/msphere.01237-20
|View full text |Cite
|
Sign up to set email alerts
|

Soil Health Management Enhances Microbial Nitrogen Cycling Capacity and Activity

Abstract: Soil microbial transformations of nitrogen (N) can be affected by soil health management practices. Here, we report in situ seasonal dynamics of the population size (gene copy abundances) and functional activity (transcript copy abundances) of five bacterial genes involved in soil N cycling (ammonia-oxidizing bacteria [AOB] amoA, nifH, nirK, nirS, and nosZ) in a long-term continuous cotton production system under different management practices (cover crops, tillage, and inorganic N fertilization). Hairy vetch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 74 publications
5
25
0
Order By: Relevance
“…AOB population dynamics were related to soil moisture in our study. The significant negative correlation of amoA gene abundance but positive correlation of amoA transcript abundance with SWC found in this study was also observed in a cotton field in the similar climatic zone ( Hu et al, 2021a ). One possible explanation was that increasing SWC decreases soil oxygen, resulting in decreased abundances of aerobic AOB.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…AOB population dynamics were related to soil moisture in our study. The significant negative correlation of amoA gene abundance but positive correlation of amoA transcript abundance with SWC found in this study was also observed in a cotton field in the similar climatic zone ( Hu et al, 2021a ). One possible explanation was that increasing SWC decreases soil oxygen, resulting in decreased abundances of aerobic AOB.…”
Section: Discussionsupporting
confidence: 84%
“…Quantitative PCR (qPCR) of AOB amoA genes and transcripts were performed on a CFX96 Optical Real-Time Detection System (Bio-Rad, Laboratories Inc., Hercules, CA, USA) using the primer pair amoA -1F (5′- GGGGTTTCTACTGGTGGT -3′) and amoA -2R (5′- CCCCTCKGSAAAGCCTTCTTC -3′) ( Rotthauwe, Witzel & Liesack, 1997 ) as we have previously described ( Hu et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Ten-fold serial dilutions (10 2 to 10 8 copies μl –1 ) of the plasmids containing nifH genes made through molecular cloning by the TOPO TA Cloning kit (Thermo Scientific, CA, United States) were used during qPCR assays to generate standard curves for quantifying nifH genes and transcripts in soil samples. Plasmids containing nifH genes amplified from environmental samples, described in our previous study ( Hu et al, 2021 ), were used as standards. Following the reactions, a melt curve analysis was performed to confirm the specificity of the PCR product.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, land tilling also affects the abundance of genes involved in several stages of nitrogen fixation [ 52 ]. Under low N fertilization (67 kg ha −1 ), Hu et al [ 53 ] reported that the relative abundance of the nif H transcript was higher in no-till soils than in conventionally tilled soils. Furthermore, the influence of soil management was also observed in the abundance of genes involved in nitrification ( amo A) and denitrification ( nor B, nir K, and nir S) in the soils.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influence of soil management was also observed in the abundance of genes involved in nitrification ( amo A) and denitrification ( nor B, nir K, and nir S) in the soils. Hu, Jin, Konkel, Schaeffer, Schneider and DeBruyn [ 53 ] studied the effects of agricultural management on the abundance of genes involved in nitrogen cycling. They observed that under N fertilizer treatment (67 kg ha −1 ), both the relative abundance and transcript of the amo A gene was increased in no-till soils.…”
Section: Discussionmentioning
confidence: 99%